Effect of celecoxib on intra-abdominal sepsis-induced lung injury in rats - Dıbekoglu, Cengiz; Bora, Ejder Saylav; Eroğlu, Ebru; Yurtsever, Guner; Uyanıkgil, Yiğit; Erbaş, Oytun (The European Research Journal, 2023)
Objectives: This experimental study investigated the preventive effects of Celecoxib, a selective COX-2 inhibitor, on lung injury induced by intra-abdominal sepsis in rats. The study assessed Celecoxib’s potential to mitigate the harmful impacts of sepsis on lung tissue. Methods: Thirty male Wistar albino rats, divided into three groups: a normal control group, a sepsis-induced group treated with saline, and a sepsis-induced group treated with Celecoxib. Sepsis was induced using fecal intraperitoneal injection (FIP), followed by a one-hour administration of Celecoxib at 50 mg/kg/day to the treatment group. Biochemical analysis of lung tissue measured oxidative stress markers (malondialdehyde [MDA]) and pro-inflammatory cytokines (Tumor Necrosis Faftor-α [TNF-α]). Histopathological examination evaluated lung tissue damage, encompassing alveolar congestion, hemorrhage, inflammatory cell aggregation, and edema. Arterial blood gas analysis quantified partial oxygen (PaO2) and carbon dioxide (PaCO2) pressures. Results: Celecoxib-treated rats exhibited reduced oxidative stress markers with lower MDA levels, indicating decreased oxidative damage in lung tissue. Moreover, TNF-α and other pro-inflammatory cytokines were significantly reduced in lung tissues of Celecoxib-treated rats, indicating its anti-inflammatory effects. Histopathological examination revealed reduced lung tissue damage in Celecoxib-treated rats, including alveolar congestion, hemorrhage, and inflammatory cell aggregation. Arterial blood gas analysis showed improved oxygenation (PaO2) in the Celecoxib-treated group compared to untreated sepsis rats. Conclusions: Celecoxib demonstrated preventive effects against sepsis-induced lung injury in rats by mitigating oxidative stress and inflammation, thereby preserving lung tissue integrity—further research, including clinical trials, to validate its effectiveness and safety in human sepsis management.